Ultrathin Films of Cellulose: A Materials Perspective - Kontturi, Eero; Spirk, Stefan (Frontiers in Chemistry, 2019)
A literature review on ultrathin films of cellulose is presented. The review focuses on different deposition methods of the films – all the way from simple monocomponent films to more elaborate multicomponent structures – and the use of the film structures in the vast realm of materials science. The common approach of utilizing cellulose thin films as experimental models is therefore omitted. The reader will find that modern usage of cellulose thin films constitutes an exciting emerging area within materials science and it goes far beyond the traditional usage of the films as model systems.